PENGARUH PEMBERIAN KEGIATAN OLAHRAGA AEROBIK TERHADAP PENURUNAN TEKANAN DARAH PADA REMAJA PENDERITA HIPERTENSI DI SMAN 10 SEMARANG - Isna Ma’rufiani Dewi; Astidio Noviardhi; Susi Tursilowati (Poltekkes Kemenkes Semarang, 2018)
Background : Hypertension in children and adolescents can be defined as Systolic Blood Pressure (TDS) / Diastolic Blood Pressure (TDD) on repeated measurements obtained from values above 95 percentiles. The incidence of hypertension in Riskesdas 2013 data for the age group 15-17 years is 5.3%. The prevalence of hypertension in adolescents in the province of Central Java in the 2013 Riskesdas data was 12.8%. Prevention of increasing the value of hypertension prevalence in adolescents can be done with aerobic exercise activities such as jogging. Objective: To determine the effect of giving aerobic exercise activities to changes in blood pressure in adolescents with hypertension. Method: Thistype of research is experimental with Randomized Control Trial Group Design. Sampling was done randomly to get 18 treatment subjects and 18 control subjects. Data collected were age, sex, weight, height, sodium intake, level of physical activity, blood pressure before and after treatment. Test the independent t-test wasused for data differences in blood pressure before and after treatment in both groups and paired t-test to determine changes in blood pressure before and after treatment, whereas the test ANOVA repeated measured is used to determine the effect of aerobic exercise (jogging)on blood pressure sample. Results: There were differences in systolic and diastolic blood pressure between the treatment and control groups (p 0.05). There is an effect of giving aerobic exercise activities to decrease systolic and diastolic blood pressure (p = 0,000 and p = 0.003) for each measurement at each meeting. Conclusion: The provision of aerobic exercise activities affects the decrease in diastolic systolic blood pressure in adolescents with hypertension.